MIRACLE FORMS IN THE NOVELS OF SARAH EDDISON ALLEN (TAMADDUN NURI JURNALI, 2024)
Article focuses on the analysis of the forms of magical realism in American Literature on the example of Sarah Addison Allen’s novels. Sarah Addison Allen is one of the outstanding writers in American literature today. Her works such as “Garden Spells” and “Sugar Queen” are highly studied by researchers. It can be observed that she tries to describe her gender views in the forms of magical realism in her novels.